The brain is the screen : Deleuze and the philosophy of cinema - Flaxman, Gregory (University of Minnesota Press, 2000)
The first broad-ranging collection on Deleuze's essential works on cinema. In the nearly twenty years since their publication, Gilles Deleuze's books about cinema have proven as daunting as they are enticing--a new aesthetics of film, one equally at home with Henri Bergson and Wim Wenders, Friedrich Nietzsche and Orson Welles, that also takes its place in the philosopher's immense and difficult oeuvre. With this collection, the first to focus solely and extensively on Deleuze's cinematic work, the nature and reach of that work finally become clear. Composed of a substantial introduction, twelve.